Botulinum toxin abdominal wall injection and post-omphalocele ventral hernia repair: database and proposal of a protocol - Lisieux Eyer de Jesus; Thais Cardoso Leve; Celine Fulgencio; Samuel Dekermacher (SpringerOpen, 2020)
Abstract Background Post-omphalocele ventral hernias (POVH) are common after giant omphaloceles. Abdominal wall botulinum toxin injections (BTI) are useful to treat complex incisional hernias (CIH) in adults, which may also apply to POVH. We review BTI data in the treatment of CIH and POVH and propose an algorithm applicable to POVH. Results Sixteen papers which described the treatment of CIH on the treatment of POVH in adults (n = 15) and children (n = 1) were reviewed. BTI elongates the lateral abdominal wall and reduces the hernia defect, with a lower incidence of compartment syndrome and respiratory complications. Doses and injection volumes vary. Effects start after 3 days, peak after 10-15 days, stabilize for 2-3 months, and decline after 4-6 months, disappearing after 6-9 months. Patients should be operated on 3-4 weeks after injection. Post-operative complications are uncommon. BTI may be associated with pre-operative pneumoperitoneum (PPP). Children presenting POVH differ from adults presenting CIH. Associated congenital cardiac malformations, genetically determined syndromes, pulmonary hypoplasia, abdominal wall hypoplasia, and thoracic dysmorphism, are common; children need sedation for any procedures; non-absorbable reinforcing meshes are not indicated; and POVH limits are frequently near to the costal margin. Conclusion BTI to induce preoperative muscular relaxation in preparation of CIH repair in adults is effective and safe. Experience with the method in children with POVH is limited, but the proposal is logical and probably safe. POVH differs from CIH in some aspects, especially abdominal wall hypoplasia, proximity to the rib cage, and diaphragmatic biomechanics.